Hepatitis B Associated Monoclonal Gammopathy That Resolved after Successful Liver Transplant - P. Sreenivasan; S. Nair (Journal of Transplantation)
Monoclonal gammopathy of undetermined significance (MGUS) has been most commonly associated with diseases like multiple myeloma, Waldenstrom's macroglobulinemia, primary systemic amyloidosis, HIV, and other lymphoproliferative disorders. There has been an isolated report of MGUS in patients coinfected with HIV and Hepatitis B, as the work by Amara et al. in 2006. Here, we report a case of IgA-kappa light chain gammopathy secondary to Hepatitis B infection, which resolved after liver transplantation. To our knowledge, this is the first reported case of M protein spike seen in the context of Hepatitis B infection only.